Variation in Rainbow Trout, Oncorhynchus mykiss, to Biosynthesize Eicosapentaenoic Acid and Docosahexaenoic Acid When Reared on Plant Oil Replacement Feeds. Issue 3 (9th June 2013) - Overturf, Ken; Welker, Tom; Barrows, Frederick; Towner, Richard; Schneider, Rich; LaPatra, Scott
Abstract To determine the potential for improving the conversion and deposition of the omega‐3 fatty acids docosahexaenoic acid (DHA; 22:6n‐3) and eicosapentaenoic acid (EPA; 20:5n‐3) in fish, 44 families of rainbow trout were fed a diet low in these components and then evaluated for their ability to convert and store plant oils that did not contain DHA and EPA in their muscle tissue. The range for EPA and DHA detected in the tissues of different families varied between 1.2 and 2.9%, and 3.8 and 7.1% total fatty acid, respectively. After adjusting for covariates, an averaged heritability of 0.78 ± 0.11 for DHA and 0.61 ± 0.17 for EPA was calculated. Expression analysis of genes related to the elongation and conversion of lipids were also analyzed, and significant differences were found in the expression of some genes between groups of families that were delineated as having relative high, medium, and low capabilities of depositing EPA and DHA in their muscle tissue after being reared on the mainly soy/flax oil containing diet. However, none of these genes showed a positive correlation with the high conversion/deposition group.